2013
DOI: 10.1152/ajpheart.00609.2012
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase-3 inhibition augments the myocardial infarct size-limiting effects of exenatide in mice with type 2 diabetes

Abstract: Glucagon-like peptide (GLP)-1 receptor activation increases intracellular cAMP with downstream activation of PKA. Cilostazol (CIL), a phosphodiesterase-3 inhibitor, prevents cAMP degradation. We assessed whether CIL amplifies the exenatide (EX)-induced increase in myocardial cAMP levels and PKA activity and augments the infarct size (IS)-limiting effects of EX in db/db mice. Mice fed a Western diet received oral CIL (10 mg/kg) or vehicle by oral gavage 24 h before surgery. One hour before surgery, mice receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…Currently available PDE3 inhibitors have little or no selectivity for PDE3A versus PDE3B, because the catalytic domains of PDE3A and PDE3B are very similar. In mice with type 2 diabetes, cilostazol enhanced the ability of exenatide and a dipeptidyl-peptidase-4 inhibitor to limit the extent of IR injury (70,71). Given these reports and our findings of cardioprotection in PDE3B −/− mice, PDE3B-selective inhibitors might provide benefit in heart transplant patients and heart failure patients, and perhaps in type 2 diabetics, by limiting I/R damage.…”
Section: Studies With Pde3amentioning
confidence: 54%
“…Currently available PDE3 inhibitors have little or no selectivity for PDE3A versus PDE3B, because the catalytic domains of PDE3A and PDE3B are very similar. In mice with type 2 diabetes, cilostazol enhanced the ability of exenatide and a dipeptidyl-peptidase-4 inhibitor to limit the extent of IR injury (70,71). Given these reports and our findings of cardioprotection in PDE3B −/− mice, PDE3B-selective inhibitors might provide benefit in heart transplant patients and heart failure patients, and perhaps in type 2 diabetics, by limiting I/R damage.…”
Section: Studies With Pde3amentioning
confidence: 54%
“…14 15 Our group has previously shown that GLP-1 receptor agonists and DPP4Is increased the production of 15-epi-lipoxin A 4 , an arachidonic acid mediator with potent anti-inflammatory and inflammation resolution properties via activation of protein kinase A and 5-lipoxygenase. 41 42 15-Epi-lipoxin A 4 suppressed activation of the inflammasome. 43 44 Thus, inhibition of the inflammasome in our models might be explained by 15-epi-lipoxin A 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect was completely blocked by PKA inhibitors, suggesting that PKA mediates the protective effect of GLP1 receptor activation (1,13).…”
mentioning
confidence: 93%
“…The precise signaling pathway for the alteration in SERCA2a expression has not yet been clarified. We have recently shown that PKA controls phosphatase and tensin homolog on chromosome 10 (PTEN) levels (1,13). PTEN degrades phosphatidylinositol 3-phosphate (PI3P) that is produced by phosphoinositide 3-kinase (PI3K).…”
mentioning
confidence: 99%